Microbial dysbiosis and lack of SCFA production in a Spanish cohort of patients with multiple sclerosis - Moles, Laura; Delgado, Susana; Gorostidi-Aicua, Miriam; Sepúlveda, Lucía; Alberro, Ainhoa; Iparraguirre, Leire; Suárez, Jose Alberto; Romarate, Leire; Arruti, Maialen; Muñoz-Culla, Maider; Castillo-Triviño, Tamara; Otaegui, David; et al. (Frontiers in Immunology, 2022)
Background Multiple sclerosis (MS) is a chronic, demyelinating, and immune-mediated disease of the central nervous system caused by a combination of genetic, epigenetic, and environmental factors. The incidence of MS has increased in the past several decades, suggesting changes in the environmental risk factors. Much effort has been made in the description of the gut microbiota in MS; however, little is known about the dysbiosis on its function. The microbiota produces thousands of biologically active substances among which are notable the short-chain fatty acid (SCFA) excretion. Objectives Analyze the interaction between microbiota, SCFAs, diet, and MS. Methods 16S, nutritional questionnaires, and SCFAS quantification have been recovered from MS patients and controls. Results Our results revealed an increment in the phylum Proteobacteria, especially the family Enterobacteriaceae, a lack in total SCFA excretion, and an altered profile of SCFAs in a Spanish cohort of MS patients. These alterations are more evident in patients with higher disability. Conclusions The abundance of Proteobacteria and acetate and the low excretion of total SCFAs, especially butyrate, are common characteristics of MS patients, and besides, both are associated with a worse prognosis of the disease.